Multiple Sacralities : Rethinking Sacralizations in European History - Brunner, Benedikt; Feindt, Gregor; Grazi, Alessandro; Groote, Inga Mai; Horstmann, Simone; Kirchhoff, Thomas; Lambert, Erin; Paulmann, Johannes; Przybylska, Lucyna; Wood, John Carter (2023)
We live in a present of multiple and conflicting sacralities. How do we account for the persistence and remarkable adaptability of traditional forms of the Christian sacred? How do we explain the ongoing allure of instrumentalizing the sacred for political purposes? And what do we make of the spread of nature spiritualities that have been so pertinent over the last half century? This volume seeks to reflect upon how these multiple sacralizations can be studied and understood in historical and cross-disciplinary perspective.